The importance of genetic factors for the development of arthropathy: a longitudinal study of children and adolescents with haemophilia A (Thrombosis and Haemostasis, 2017)
Haemophilia A is a congenital bleeding disorder characterised by recurrent haemorrhages into the major joints. Haemophilic arthropathy is a well-established outcome of recurrent joint bleeding; however, it is clear that multiple factors determine the extent and severity of its occurrence. We sought to identify genetic factors related to abnormalities in range of motion (ROM) in the knees, ankles and elbows in a cohort of children and adolescents with haemophilia A not treated primarily with regular prophylaxis. Using data from the Haemophilia Growth and Development Study, we examined associations between 13,342 genetic markers and ROM scores measured at six-month intervals for up to seven years. As a first step, ordered logistic regression models were fit for each joint separately. A subset of SNP markers showing significant effects (p<0.01) on the right and left sides for at least two joints were included in a full model fit using a multivariate generalised linear mixed model assuming an ordinal response. The models contained all ROM scores obtained at all visits. Twenty-five markers analysed in the full model showed either increased or decreased risk of ROM abnormalities at the p<0.001 level. Several genes identified at either the first or second stage of the analysis have been associated with arthritis in a variety of large studies. Our results support the likelihood that risk for haemophilic arthropathy is associated with genetic factors, the identification of which holds promise for further advancing the individualisation of treatment.
Keywords: Genetics; haemophilia; haemarthrosis; joint range of motion; arthritis